Membedah Perbedaan Antara Ekonomi Syariah dan Ekonomi Konvensional - Khairunnisa Khairunnisa; Rahmi Sekar Andhini (Journal of Islamic Economics and Finance, 2025)
This study uses a qualitative method and aims to dissect the differences between Islamic economics and conventional economics. This study found that Islamic economics is based on Islamic principles reflected in the Qur’an and Hadith, emphasizing social justice, balance, and avoiding elements of usury, gharar, and maysir in every economic activity. Meanwhile, conventional economics is based on the principles of a market economy that aims to maximize material profits without considering spiritual or moral aspects. The source of conventional economic law comes from rules made by humans, while Islamic economics refers to the law of Allah. The Islamic financial system uses profit- sharing mechanisms and halal investments, while the conventional system relies on interest as the main source of income. In addition, Islamic economics integrates social instruments such as zakat, infaq, and sedekah for wealth redistribution, while conventional economics emphasizes taxes and government policies. Thus, this study confirms that the fundamental differences between the two systems lie in their philosophical foundations, objectives, and operational mechanisms.